Case Report: Novel Anchoring Technique and Surgical Nuances for Trigeminal Ganglion Stimulation in the Treatment of Post-Herpetic Trigeminal Neuropathic Facial Pain - Gupta, Kunal (Frontiers in Pain Research, 2022)
Introduction Trigeminal ganglion stimulation is a neuromodulatory surgical procedure utilized to treat trigeminal neuropathic pain. This technique involves the placement of a stimulating electrode adjacent to the trigeminal ganglion and can be trialed before permanent implantation. Wider adoption by surgical practitioners is currently limited by complications such as lead migration from the trigeminal ganglion, which can result in loss of therapy and cannot be rectified without repeat surgery. We describe a novel surgical modification that successfully anchors the trigeminal ganglion electrode long-term. Objective To describe a novel surgical technique for the anchoring of trigeminal ganglion stimulation electrodes and a case report of a patient with post-herpetic trigeminal neuropathic pain treated with this approach. Methods An electrode was inserted percutaneously through the foramen ovale into Meckel's cave, adjacent to the trigeminal ganglion. The lead was anchored using a modification of an existing anchoring device, which was inserted into the buccal incision. The lead was connected to a generator for therapeutic stimulation. The location of the lead was followed radiographically using serial lateral skull radiographs. Results A 74-year-old male with post-herpetic trigeminal neuropathic pain, who had failed prior surgical therapies, underwent trigeminal ganglion stimulation. The trial lead was anchored using standard techniques and migrated outward within 7 days, rendering the trial electrode ineffective. The permanent lead was anchored using the described novel technique and remained in position without clinically significant outward migration nor loss in targeted stimulation until the last follow-up at 6 months. Conclusion Trigeminal ganglion stimulation is an effective therapeutic option for medically refractory trigeminal neuropathic pain. The novel surgical adaptation described prevents the outward migration of the lead and enables stable long-term lead placement.